KOMERSIALISASI KOMODITAS PERTANIAN ORGANIK SEBAGAI ALTERNATIF PEMULIHAN EKONOMI PADA PETANI DI DATARAN TINGGI DIENG - Dyah Sugandini; Mohamad Irhas Effendi; Siwi Hardiastuti Endang Kawuryan; Bambang Sugiarto; Muhammad Kundarto (Dharma: Jurnal Pengabdian Masyarakat, 2023)
The community service program, packaged in the Kedaireka Matching Fund (MF), aims to help farmers to be able to commercialize their agricultural products. There are two outcomes of this Kedaireka-MF community service: an organic fertilizer factory and a frozen vegetable factory. Several methods are carried out to support the creation of commercialization. The Kedaireka-MF community service program starts with commercialization socialization, assistance in making organic fertilizers, assistance in making frozen vegetable factories, and assistance in digital marketing. Digital marketing platforms that can be made are websites, Instagram and YouTube. Kedaireka-MF has also registered its products through the Shopee e-commerce platform. To improve the quality of commercialization, the Kedaireka-MF community service program has started a new business with a legal entity, CV Reka Tani Mandiri. This MSME company was established as a forum for farmers to commercialize agricultural products in a professional manner.